Holistic approach to the treatment of cervical spine pain syndromes - Juraszek, Karolina Małgorzata; Molski, Paweł; Ziemniarska, Barbara; Kucharczuk-Kopycińska, Magda; Kalisz, Justyna; Goch, Aleksander (Journal of Education, Health and Sport, 2017)
Abstract Spinal pain, including the cervical spine, is currently one of the most common causes of patient visits to physiotherapy clinics. The pursuit for material goods of modern society, stress, lack of time for physical activities and effective rest or staying most of the day in forced sitting position (at work, at home, in the car) are causes for such trends. Extremely important at the very beginning of the planning of the therapy process is the analysis of the underlying dysfunction that may have different origins. The very visual assessment of the patient’s posture pattern during the first visit to the clinic provides valuable information, such as emotional state or positioning of individual body parts, which is important for the progress of therapy and the sustainability of improvement. The article presents a new perspective on the pain of the cervical spine as a disorder of the fascia, requiring tissue and emotional integration. Based on Kinesis Myofascial Integration (KMI), the anatomy trains (musculoskeletal chains), attention focuses on the essential components of cervical dysfunction therapy that may appear to be completely unrelated to the dysfunction seen only through the traditional treatment (symptomatic).